A doubly invisible aquifer: Hydrogeological studies and actors’ strategies in the Pampa del Tamarugal aquifer, northern Chile - Elisabeth Lictevout (Water Alternatives, 2018)
In northern Chile groundwater resources are used intensively for mining activities, drinking water and agriculture. This article analyses the groundwater management in the Pampa del Tamarugal Aquifer, paying special attention to the links between (a) how information relating to groundwater resources and its uses is applied to management and (b) actors’ strategies and discourses on groundwater management. The analysis focuses on two moments: the decision to stop issuing new water rights and the short-lived experience of a regional water resources research centre. Actors never actually discussed an appropriate groundwater pumping rate and some used groundwater resources as a means of pursuing strategies that were not related to water management per se. Many called for a participatory process to allocate water for different uses, although this would entail changes to Chilean legislation. Such a process would help the Pampa del Tamarugal Aquifer become more 'visible' and could trigger genuine discussion about the status and use of groundwater resources.